ANALISIS PENGARUH MOTIVASI, KOMITMEN DAN GAYA KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU MADRASAH ALIYAH AL KAUTSAR PANDAAN KABUPATEN PASURUAN - jurnalpps pps; Akhmad Subhan Suyuthi; Indra Prasetyo; Mei Indrawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study was to test the motivation, commitment and leadership style on the performance of Madrasah Aliyah Al Kautsar teachers partially and simultaneously. The population in this study were all teachers with a total of 31 respondents, and was a census sampling study. The results showed that either partially or simultaneously the variables of motivation, commitment and leadership style had a significant influence on the performance of Madrasah Aliyah Al Kautsar Pandaan teachers. In an effort to improve the performance of Madrasah Aliyah Al Kautsar teachers, it is by increasing motivation, commitment and leadership style, as well as evaluating performance results and providing awards for teachers.